PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI TERHADAP MOTIVASI BELAJAR SISWA SMA NEGERI 5 BALIKPAPAN - Prawara, Anandhito Wisnu; Hidayat, Muhammad Raihan; Riski Zulkarnain; Idris, Nasruddin Bin Idris (REKADATA, 2026)
The rapid digital transformation in the educational sector has fundamentally shifted the learning paradigm toward more interactive, technology-integrated pedagogical methods. This research aims to critically analyze the impact of technology-based interactive learning media on the learning motivation of students at SMA Negeri 5 Balikpapan, grounded in the ARCS (Attention, Relevance, Confidence, Satisfaction) motivational framework and Mayer’s Cognitive Theory of Multimedia Learning. Employing a quantitative approach with a cross-sectional survey design, this study gathered empirical data from 43 eleventh-grade students using a high-precision structured questionnaire. The research instrument was subjected to rigorous psychometric evaluation, including Pearson Product Moment for construct validity and Cronbach’s Alpha to ensure internal consistency and reliability. Statistical analysis, processed via simple linear regression, yielded a robust correlation with an R-square value of 0.693. These findings demonstrate that the strategic implementation of interactive digital tools accounts for 69.3% of the variance in student motivation, indicating a significant positive influence. The study underscores that multisensory digital interaction effectively bridges the engagement gap in traditional classrooms. Consequently, these results provide a strong empirical basis for educators to prioritize the integration of dynamic digital resources to foster a sustainable and high-quality instructional environment in secondary education.